Literarnozgodovinska recepcija Primoža Trubarja - Štuhec, Miran (Slavia Centralis, 2020)
Literary historical reception of Primož Trubar Slovenian Protestants began the centuries-long process of the recognition of the Slovenians – not only as a linguistic entity but also as a national body. Essentially, it is about their cultural and civilizational mission, which for the first time clearly articulated the Slovenians in the cultural and linguistic sense within European history. The analysis of the selected literary historical papers showed that the Slovenian literary science dealt with Primož Trubar (and Slovenian Protestantism) mostly in two ways. First, as literary syntheses and second, as researching individual, more or less complex problem circles, which formed at the emergence of reformation in Slovenia.